Videos Relacionados

Encontrar la derivada $\frac{d}{dx}\left(e^{2x}-x\cos\left(xy\right)\right)$ usando la regla de la suma

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Calculus - Find the derivative of natural logarithm using product property, d(ln(2x))/dx

https://www.youtube.com/watch?v=urYZhqwUTI0

Calculus - Implicit differentiation using the chain and product rule with cosine, d(cos(xy))/dx

https://www.youtube.com/watch?v=Rd-pluTxOt8

Calculus - Using the chain rule to take the derivative of an exponential equation, d(e^(5x))/dx

https://www.youtube.com/watch?v=4h5bDyy_03A

Proof: d/dx(e^x) = e^x | Taking derivatives | Differential Calculus | Khan Academy

https://www.youtube.com/watch?v=sSE6_fK3mu0

Proof: d/dx(ln x) = 1/x | Taking derivatives | Differential Calculus | Khan Academy

https://www.youtube.com/watch?v=yUpDRpkUhf4

Calculus - Implicit differentiation using the product rule, d(xy^2)/dx

https://www.youtube.com/watch?v=ADLy8Kvu1WI
$\frac{d}{dx}\left(e^{2x}-x\cdot \cos\left(xy\right)\right)$

Tema principal:

Derivada de la Suma

Fórmulas Relacionadas:

5. Ver fórmulas

Tiempo para resolverlo:

~ 0.05 s